A Lesson Learned: How SMEs Build Dynamic Capability during Covid-19 Pandemic - Laksana, Dwi Hari; Sutiono, Heru Tri; Kusmantini, Titik; Diantoro, Aris Kusumo (RSF Conference Series: Business, Management and Social Sciences, 2021)
The COVID-19 pandemic has had a significant impact on SME business sustainability. Some SMEs are no longer operating because the pandemic has triggered a number of business risks for them. In order to survive, SMEs are required to develop elements of dynamic capabilities for their own businesses. This research aims to explore in-depth how SMEs build the microelements of their dynamic capabilities during the COVID-19 pandemic. The authors used the case study method as research design by selecting 4 SMEs that represent the industrial center village in Wedi and Bayat Districts, Klaten Regency. In order to analyze, the authors in this research used the triangulation technique, and data collection is done by making visits to companies, observations, and interviews with a number of key informants who understand the development of the craft industry in Klaten Regency. This research focused on identifying critical elements that proved to be effective to support their business through the pandemic by implementing the abilities of sensing, seizing, and transforming. Sensing ability is the ability to target new market segments and new business opportunities. Seizing ability is the ability to produce new products that customers really need. Meanwhile, the ability to transforming is the most powerful capability carried out so far by SMEs by managing more agile businesses with innovative marketing practices.